L'elisió de la /R/ final de mot en tortosí meridional - Gimeno Betí, Lluís (Caplletra. Revista Internacional de Filologia, 2015)
This paper contributes dialect data on the loss of word-final /r/ in a transitional area that the author call «Tortosí meridional». The author also includes diachronic data taken from interesting non-literary works in his discussion of the maintenance or deletion of the phoneme.